Jewish education and society in the high middle ages - Ḳanarfogel, Efrayim 1955- (Wayne State Univ. Pr., 1992)
Kanarfogel examines the educational process in Ashkenaz, exploring whether there was a developed system of education, whether compensation for Torah study was permitted
Keywords: Geschichte 1100-1300; Godsdienstige opvoeding; Hassidisme médiéval; Joden; Jodendom; Juifs - Allemagne - Histoire - 1096-1800; Juifs - Allemagne - Vie intellectuelle; Juifs - France (Nord) - Vie intellectuelle; Juifs - Savoir et érudition - Allemagne; Juifs - Savoir et érudition - France (Nord); Late middeleeuwen; Tossafistes; Éducation religieuse juive - Allemagne - Histoire; Éducation religieuse juive - France (Nord) - Histoire; Geschichte; Juden; Judentum; Hasidism, Medieval; Jewish learning and scholarship -- France, Northern; Jewish learning and scholarship -- Germany; Jewish religious education -- France, Northern -- History; Jewish religious education -- Germany -- History; Jews -- France, Northern -- Intellectual life; Jews -- Germany -- History -- 1096-1800; Jews -- Germany -- Intellectual life; Tosafists; Jüdische Erziehung; Mittelalter; Religiöse Erziehung; Allemagne - Relations interethniques; France (Nord) - Relations interethniques; Deutschland; France, Northern -- Ethnic relations; Germany -- Ethnic relations; Westeuropa